(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Hate crime victims are often unable to seek redress against perpetrators for a variety of reasons, meaning many crimes remain unreported, unprosecuted and, ultimately, invisible. In such cases, the rights of victims of crime may not be fully respected and EU Member States may not be upholding their obligations towards victims of crime and society in general. FRA’s work on hate crime and on the rights of victims of such crime has consistently found that the criminal justice system’s response to hate crime is significantly affected when victims encounter difficulties in reporting, and, in many cases, by the police’s, public prosecutors’ and criminal judges’ reluctance to record and acknowledge hate crime. FRA’s victimization surveys – which collected victim views on racist and xenophobic, 6 LGBTI-related 7 and antisemitic crimes,8 as well as on the experiences of women as victims of violence 9 – examined the reasons for these difficulties from the perspective of victims.